Platystele finleyae (Pleurothallidinae), a new species from northwestern Ecuador - Monteros, Marco F.; Restrepo, Eugenio; Baquero, Luis E. (Lankesteriana: International Journal on Orchidology, 2022)
A new species of Platystele from northwestern Ecuador is described and illustrated. The new species, Platystele finleyae, belongs to the “pubescens” morphological informal group of species, and it is similar to P. ximenae in the broad flowers with pubescent sepals and petals but is easy distinguished by the vermilion to vinaceous flowers (vs. yellow, suffused with purple at the basal middle) and long ciliate petals (vs. shortly pubescent in P. ximenae). Platystele finleyae was found near Dracula Reserve, and it is named in honor of Elizabeth Finley Broaddus, who inspires many people, especially the youth, in environmental conservation. In addition, information is provided on its distribution, habitat, and conservation status.